HrpL regulon of bacterial pathogen of woody host Pseudomonas savastanoi pv. Savastanoi NCPPB 3335 - Moreno-Pérez, Alba; Ramos-Rodríguez, Cayo Juan; Rodríguez-Moreno, Luis Gabriel (MDPI, 2021)
The Pseudomonas savastanoi species comprises a group of phytopathogenic bacteria that cause symptoms of disease in woody hosts. This is mediated by the rapid activation of a pool of virulence factors that suppress host defences and hijack the host’s metabolism to the pathogen’s benefit. The hrpL gene encodes an essential transcriptional regulator of virulence functions, includ-ing the type III secretion system (T3SS), in pathogenic bacteria. Here, we analyzed the contribution of HrpL to the virulence of four pathovars (pv.) of P. savastanoi isolated from different woody hosts (oleander, ash, broom, and dipladenia) and characterized the HrpL regulon of P. savastanoi pv. savas-tanoi NCPPB 3335 using two approaches: whole transcriptome sequencing (RNA-seq) and the bio-informatic prediction of candidate genes containing an hrp-box. Pathogenicity tests carried out for the P. savastanoi pvs. showed that HrpL was essential for symptom development in both non-host and host plants. The RNA-seq analysis of the HrpL regulon in P. savastanoi revealed a total of 53 deregulated genes, 49 of which were downregulated in the ΔhrpL mutant. Bioinformatic prediction resulted in the identification of 50 putative genes containing an hrp-box, 16 of which were shared with genes previously identified by RNA-seq. Although most of the genes regulated by HrpL be-longed to the T3SS, we also identified some genes regulated by HrpL that could encode potential virulence factors in P. savastanoi.
Keywords: Bacterias fitopatógenas; Plantas leñosas - Enfermedades bacterianas; P. savastanoi pv. savastanoi (Psv); Type III secretion system (T3SS); HrpL regulon; RNA-seq analysis; Hrp-box prediction; Virulence factors